Controlling PA6/PET adhesion to facilitate interfacial fracture. (15th May 2022) - Machikiti, Zvikomborero; Pourdeyhimi, Behnam; Genzer, Jan; Efimenko, Kirill
Graphical abstract: Highlights: The increased adhesion in poly(ethylene terephthalate) (PET)/Nylon 6 (PA6) bicomponent fibers due to the processing conditions causes significant challenges in fiber processing. The interfacial reaction can be controlled by the addition of maleic anhydride alternating copolymers. The adhesion strength is regulated by the concentration and chemical composition of a maleic copolymer, the blend annealing temperature, and reaction time. Abstract: Microfibers get often produced in the form of bicomponent polymer systems. The materials of choice are Nylon 6 (PA6) and poly(ethylene terephthalate) (PET). This combination of PA6 and PET is preferable because of its beneficial attributes ( i.e., thermal stability, mechanical strength, etc.). PA6 and PET exhibit high adhesion when processed at elevated temperatures due to chemical bonds formation by aminolysis of the ester group in PET with a secondary amine in PA6. These fibers are split/fibrillated by mechanical energy (hydroentangling or needle punching). For energy input, it is desirable to have adhesion between the PA6 and PET materials that is not too strong to allow for easy polymer splitting. Therefore, we developed a method for tailoring the PA6/PET interface adhesion by adding modifiers that react preferentially with the PA6 component. The reactivity between PA6 and PET was investigated by spin coating thin films of PA6 and PET on silicon wafers and annealing them at high temperatures. The reaction between PET and small molecules containing secondary amines ( i.e., caprolactam, diallyamine, diethylamine, and diisopropylamine) shows a chemical bond between the ester group in PET and the secondary amine group. The poly(styrene-alt-maleic anhydride) (PSMA) and poly(octadecene-alt-maleic anhydride) (POMA) were chosen as model polymer interfacial modifiers. The feasibility of modifying secondary amines is examined by reacting the two modifiers, PSMA and POMA, with small molecules containing secondary amine groups. PA6 and PET display high fracture toughness ( i.e., adhesion strength) at elevated temperatures and longer annealing times because of strong interactions between the amine and ester groups in PA6 and PET, respectively. We then assess the adhesion strength between PA6 and PET modified with PSMA and POMA. Both modifiers reduce interfacial adhesion strength between PA6 and PET. Therefore, it is feasible to tailor adhesion at the PA6/PET interface, which could prove helpful in microfibers production.